Islam's Response to Tradition and Modernity: The Integration of Global Values, Technology, and Civilization - Pahlevi, Akhmed Reza; Nakazima, Dendi Eriyan Ihza; Nursalim, Eko (IJoIS: Indonesian Journal of Islamic Studies, 2025)
Islam is continuously engaged with diverse traditions, cultures, ethnic groups, races, and civilizations, including the dynamics of modernization, which is marked by technological progress and the swift circulation of information. The purpose of this study is to explore the concepts, challenges, and critical perspectives on tradition and modernity within Islamic thought. This paper employs a literature review method with a descriptive qualitative approach, gathering data and insights from a range of references such as books, scholarly articles, journals, and other relevant sources. The results show that Islam provides a selective response based on the principle of adopting new, beneficial ideas without abandoning good old traditions. Islam encourages the use of technology for da'wah (Islamic outreach), the integration of religious curricula with science, the development of sharia economics as an alternative to capitalism, the filtering of modern ideas, and an active contribution to creating a balanced global civilization.